1996
DOI: 10.1002/(sici)1097-0142(19960415)77:8<1501::aid-cncr12>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel tumor-associated antigen expressed in human uterine and ovarian carcinomas

Abstract: BACKGROUND.A large number of monoclonal antibodies (MoAhs) against human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
124
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 38 publications
4
124
0
Order By: Relevance
“…In gynaecological malignancies, Kaku et al (1999) reported that patients with high RCAS1 expression showed significantly worse overall survival than those with low expression in adenocarcinoma of uterine cervix. In addition, Sonoda et al (1998) reported that RCAS1 was not detected in the normal uterine cervix or ovarian tissue, but strongly expressed in uterine endometrial adenocarcinomas, ovarian adenocarcinomas (Sonoda et al, 1996;Sonoda et al, 2000) and cervical squamous cell carcinomas. Recently, Suzuki et al (2001) reported that EBAG9 immunoreactivity was detected in 82 of 91 in breast carcinoma (90.1%), although it was not associated with clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gynaecological malignancies, Kaku et al (1999) reported that patients with high RCAS1 expression showed significantly worse overall survival than those with low expression in adenocarcinoma of uterine cervix. In addition, Sonoda et al (1998) reported that RCAS1 was not detected in the normal uterine cervix or ovarian tissue, but strongly expressed in uterine endometrial adenocarcinomas, ovarian adenocarcinomas (Sonoda et al, 1996;Sonoda et al, 2000) and cervical squamous cell carcinomas. Recently, Suzuki et al (2001) reported that EBAG9 immunoreactivity was detected in 82 of 91 in breast carcinoma (90.1%), although it was not associated with clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that RCAS1 is associated with poor prognosis and/or advanced stage in various human cancers (Sonoda et al, 1996;Kaku et al, 1999;Izumi et al (2001); Nakakubo et al, 2002). However, the expression of EBAG9 and its clinical significance have not been examined in epithelial ovarian cancer.…”
mentioning
confidence: 99%
“…Immunohistochemically, expression of RCAS1 has been detected in uterine and ovarian carcinomas, especially in invasive tumors (10,11). However, RCAS1 has not been detected in normal uterine and ovarian tissues (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, RCAS1 has not been detected in normal uterine and ovarian tissues (10). In addition, RCAS1 is highly expressed on invasive carcinomas (11), and expression of RCAS1 is correlated with poor prognosis in uterine cancers (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation